Legitimacy of international criminal tribunals - Hayashi, Nobuo; Bailliet, Cecilia; Nicholson, Joanna (Cambridge : Cambridge University Press, 2017)
With the ad hoc tribunals completing their mandates and the International Criminal Court under significant pressure, today's international criminal jurisdictions are at a critical juncture. Their legitimacy cannot be taken for granted. This multidisciplinary volume investigates key issues pertaining to legitimacy: criminal accountability, normative development, truth-discovery, complementarity, regionalism, and judicial cooperation. The volume sheds new light on previously unexplored areas, including the significance of redacted judgements, prosecutors' opening statements, rehabilitative processes of international convicts, victim expectations, court financing, and NGO activism. The book's original contributions will appeal to researchers, practitioners, advocates, and students of international criminal justice, accountability for war crimes and the rule of law.
The legitimacy of international criminal tribunals / Larry May and Shannon Fyfe -- Conceptualising and measuring the legitimacy of international criminal tribunals / Silje AA. Langvatn and Theresa Squatrito -- Between international criminal justice and injustice : theorising legitimacy / Sergey Vasiliev -- Legitimacy, legality, and the possibility of a pluralist international criminal law / Asad Kiyani -- The legitimacy and effectiveness of international criminal tribunals : a criminal policy perspective / Athanasios Chouliaras -- Legitimacy and ICC jurisdiction following security council referrals : conduct on the territory of non-party states and the legality principle / Rogier Bartels -- Is the Yugoslav Tribunal guilty of hyper-humanising international humanitarian law? / Nobuo Hayashi -- 'One of the challenges that can plausibly be raised against them'? on the role of truth in debates about the legitimacy of international criminal tribunals / Jakob V.H. Holtermann -- Hidden legitimacy : crafting judicial narratives in the shadow of secrecy at a War Crimes Tribunal : a speculation / Timothy William Waters -- Positive complementarity and legitimacy : is the international criminal court shifting from judicial restraint towards intervention? / Ignaz Stegmiller -- African supranational criminal jurisdiction : one step towards ending impunity or two steps backwards for international criminal justice? / Dorothy Makaza -- Legitimacy defects and legal flaws of the special tribunal for lebanon : dilemmas of the 'peace through justice' theorem / Martin Wahlisch -- Prosecutors' opening statements : the rhetoric of law, politics and silent war / Damien Rogers -- Effectiveness of international criminal tribunals : empirical assessment of rehabilitation as sentencing goal / Barbora Hola, Jessica Kelder, and Joris van Wijk -- Procedural justice, legitimacy, and victim participation in Uganda / Stephen Smith Cody -- Things fall apart : battles of legitimation and the politics of noncompliance and African sovereignty from the Rwanda Tribunal to the ICC / Victor Peskin -- Financing lady justice : how the funding systems of Ad Hoc Tribunals could lend themselves to the possibility of judicial bias / Mistale Taylor -- Claiming authority in the name of the other : human rights NGOs and the ICC / Kjersti lohne.
Title from publisher's bibliographic system (viewed on 10 Aug 2017).
Includes bibliographical references and index.
Keywords: International Criminal Court; International Criminal Court; International criminal courts; International criminal courts